New locality record of Monaxinoides austrosinensis (Mazocraeidea, Monaxinoididae) of finlet crevalle, Atule mate (Perciformes: Carangidae) from the Gulf of Thailand - Intamong, Jittikan; Keawviyuth, Smarn; Yooyen, Thanapon; Chantima, Kittichai (Agriculture and Natural Resources, 2016)
Out of 203 Atule mate fish specimens examined, only 23 had parasitic monogeneans, Monaxinoides austrosinensis from the Gulf of Thailand. The prevalence and intensity of infection were 12.81% and 1.27%, respectively. Morphologically, the leaf-like body of M. austrosinensis was 5.88-8.07 mm long and 1.84 -3.34 mm wide with a faneshaped opisthohaptor at the posterior end. Numerous pores on the body tegument were observed using scanning electron microscopy. The muscular structure around the vaginal pore presented a number of sensory papillae. The opisthohaptor was one row of clamps which appeared similar in size. The presence of M. austrosinensis in this study is a new locality record in Thailand and is the first description based on scanning electron microscopy.